Management of pneumonitis post-concurrent chemoradiation and immunotherapy in patients with advanced lung cancer: Case report and litterature review - Hung, Nguyen Van; Tan, Nguyen Nhat; Manh, Pham Duy; Bach, Tran Trung; Huy, Trinh Le (Tạp chí Nghiên cứu Y học, 2024)
Immune-related pneumonitis is a rare but serious complication in patients with non-small cell lung cancer (NSCLC) treated with durvalumab after concurrent chemoradiotherapy (CRT). We encountered a 61-year-old male with stage III non-small cell lung cancer (NSCLC) receiving concurrent chemoradiotherapy followed by durvalumab maintenance therapy. After 1 cycle of durvalumab treatment, he developed progressive dyspnea, dry cough, and low-grade fever. Chest CT scans revealed diffuse ground-glass opacities in both lungs, indicative of immune-related pneumonitis. Durvalumab was discontinued, and the patient was treated with high-dose corticosteroids and antibiotics. After one month, he fully recovered. Durvalumab was cautiously resumed under close monitoring without recurrence of pneumonitis. Conclusion: Early identification and management of immune-related pneumonitis are essential in NSCLC patients receiving durvalumab. Reintroducing durvalumab after recovery may be safe with vigilant monitoring.